Increasing participation in a vector control campaign: a cluster randomised controlled evaluation of behavioural economic interventions in Peru. Issue 5 (21st September 2018) - Buttenheim, Alison M; Paz-Soldán, Valerie A; Castillo-Neyra, Ricardo; Toledo Vizcarra, Amparo M; Borrini-Mayori, Katty; McGuire, Molly; Arevalo-Nieto, Claudia; Volpp, Kevin G; Small, Dylan S; Behrman, Jere R; Naquira-Verlarde, Cesar; Levy, Michael Z
Abstract : Objective: To assess the efficacy of strategies informed by behavioural economics for increasing participation in a vector control campaign, compared with current practice. Design: Pragmatic cluster randomised controlled trial. Setting: Arequipa, Peru. Participants: 4922 households. Interventions: Households were randomised to one of four arms: advanced planning, leader recruitment, contingent group lotteries, or control. Main outcome measures: Participation (allowing the house to be sprayed with insecticide) during the vector control campaign. Results: In intent-to-treat analyses, none of the interventions increased participation compared with control (advanced planning adjusted OR (aOR) 1.07 (95% CI 0.87 to 1.32); leader recruitment aOR 0.95 (95% CI 0.78 to 1.15); group lotteries aOR 1.12 (95% CI 0.89 to 1.39)). The interventions did not improve the efficiency of the campaign (additional minutes needed to spray house from generalised estimating equation regressions: advanced planning 1.08 (95% CI −1.02 to 3.17); leader recruitment 3.91 (95% CI 1.85 to 5.97); group lotteries 3.51 (95% CI 1.38 to 5.64)) nor did it increase the odds that houses would be sprayed in an earlier versus a later stage of the campaign cycle (advanced planning aOR 0.94 (95% CI 0.76 to 1.25); leader recruitment aOR 0.68 (95% CI 0.55 to 0.83); group lotteries aOR 1.19 (95% CI 0.96 to 1.47)). A post hoc analysis suggested that advanced planning increased odds of participation compared with control among households who had declined to participate previously (aOR 2.50 (95% CI 1.41 to 4.43)). Conclusions: Achieving high levels of household participation is crucial for many disease prevention efforts. Our trial was not successful in improving participation compared with the existing campaign. The trial highlights persistent challenges to field experiments as well as lessons about the intervention design process, particularly understanding barriers to participation through a behavioural lens. Trial registration number: American Economic Association AEARCTR-0000620.